FRI0260 Survival, causes of death and mortality risk factors in systemic sclerosis. (23rd January 2014) - Ovalles-Bonilla, J.G.; Martínez-Barrio, J.; Lόpez-Longo, F.; de la Torre, I.; González, C.; Valor, L.; Montoro-Άlvarez, M.; Aramburu, F.; Marín, C.; Martínez-Estupiñán, L.; Nieto, J.; Hinojosa, M.; et al.
Abstract : Background: Among the rheumatic diseases, Systemic Sclerosis (SSc) stands out as a severely incapacitating and life-threatening disease. Objectives: To analize the causes of death, survival and risk factors for mortality in SSc patients. Methods: Demographic, clinical, immunological and mortality data were obtained from a long term prospective cohort of SSc patients recruited between 1986 and 2011 in the Rheumatology Department of Gregorio Marañon Hospital in Madrid, Spain. Patients were divided into 4 groups: limited SSc, diffuse SSc, SSc in overlap and SSc in mixed connective tissue disease (SSc-MCTD). ANOVA, Kruskal-Wallis or χ 2 tests were used to identify differences among groups; Kaplan-Meier and Mantel-Haenszel (log-rank) analysis were used to estimate survival, and Cox proportional hazards regression analysis was used to identify factors associated with mortality. Results: A total of 137 patients were included, of whom 122 (89%) were women. Mean age at diagnosis was 43±17.7 years, and the mean follow-up time was 15.2 years. A global mortality of 34 (24.8%) cases was observed: 8 related to cardiac involvement, 8 to serious infections, 7 to pulmonary involvement, 6 to neoplasms, 2 to renal involvement and 3 to other causes. Survival rates from disease onset were 96, 90, 75 and 50% at 5, 10, 20 and 30 years, respectively. Limited SSc and SSc-MCTD show a significantly (p=0.002) higher survival mean time (33.7 years) when compared to diffuse and overlap variants (22.4 years). Poorer survival is associated with interstitial lung disease, pulmonary arterial hypertension, severe infections, cardiac involvement, chronic kidney disease, and Anti-Ro antibodies (see table 1 ). Independent prognostic factors for mortality were interstitial lung disease (HR 6.8, CI 95% 1.5-30, p=0.012), pulmonary arterial hypertension (HR 5.6, CI 95% 1.2-26.9, p=0.032), and Anti-Ro antibodies (HR 3.9, CI 95% 1.5-9.8, p=0.004). Conclusions: A 20-year survival was seen in more than 70% of SSc patients. The main causes of death are cardiac involvement, severe infections and pulmonary manifestations. Diffuse SSc, SSc-MCTD, interstitial lung disease, pulmonary arterial hypertension, severe infections, cardiac involvement, chronic kidney disease, and Anti-Ro antibodies are the main risk factors for mortality. Disclosure of Interest: None Declared